Foes can be friends: laboratory trials on invasive apple snails, Pomacea spp. preference to invasive weed, Limnocharis flava (L.) Buchenau compared to rice, Oryza sativa L. - Ahmed Gilal, Arfan; Muhamad Awang, Rita; Omar, Dzolkhifli; Abdul Aziz, Nor Azwady; Gnanasegaram, Manjeri (Smith and Franklin Academic Publishing, 2016)
Rice ecosystem often involves a complex interaction of various pest species with rice. An example of such interaction is that between the invasive Pomacea spp. and Limnocharis flava. Both invasive pests have caused heavy loss to rice in Southeast Asia including Malaysia. However, information on the interaction of both invasive pests in the rice field is still lacking. Therefore, a laboratory study was conducted to determine the feeding preference and growth pattern of P. canaliculata and P. maculatafor rice and L. flava based on choice and no-choice experiments. It was found that the three different sizes (1, 2 and 3cm) of both Pomacea spp. used in this study showed significantly less preference for rice stems and leaves as compared to L. flava leaves and stems. Among all the studied plant materials, rice stems were the least consumed. Moreover, higher shell length growth and weight gain was also recorded in the two species when fed with L. flava. This further suggests that the two Pomacea spp. have the potential to be used as an effective bio-control agent against the invasive weed in the rice ecosystem during the early stages of rice growth, in combination with a proper management of irrigation water. In addition, L. flava can also be used as a trap crop in rice fields to ease the collection and destruction of apple snails.